AI, Data, and Digitalization: First International Symposium, SAIDD 2023, Sogndal, Norway, May 9–10, 2023, Revised Selected Papers - Akerkar, Rajendra (Communications in Computer and Information Science, 2024)
This open access book constitutes the revised selected papers of the First International Symposium on AI, Data and Digitalization, SAIDD 2023, held in Sogndal, Norway, during May 9–10, 2023. The 13 full papers included in this volume were carefully reviewed and selected from 42 submissions. The papers deal with the impact of data and AI on the digital revolution and their contribution to solving societal challenges.